Providing flexibility in the Vehicle Route Optimization for the AVL-based Transport Monitoring System - MASROM, S. (2010)
Automated Vehicle Location (AVL) based Transport Monitoring System (TMS) has generated some interest within the research community since decades ago. The emergence of enabling technologies such as the Global Positioning System (GPS) and advanced cellular communication systems has opened up new opportunity to this area of research. Vehicle location is now determined in real time and data can be transferred instantaneously to either centralized or decentralized processors. Implementation of a full fledge TMS requires components such as communication module, Geographical Information System (GIS), databases and monitoring application to be incorporated into the system architecture. Once all the elements are gathered, the project will inevitably become very complex and difficult to deploy efficiently and in a timely manner. In this paper, we propose a new approach for the design and implementation of a TMS. The approach that we are proposing relies on the strength and modular nature of a language-based platform. The platform will not only make the project more manageable but will also enhance it by offering extended collaborative features. It will also allow modular experimentation of various optimization algorithms in different Vehicle Routing Problem (VRP) model to be designed and tested for better system performance. With the proposed framework, AVL based TMS can be built economically and efficiently. Analysis and comparison among current AVL based systems are also performed in order to investigate the feasibility of the project.